Status of Macrophomina phaseolina on Strawberry in California and Preliminary Characterization of the Pathogen. (30th November 2016) - Koike, Steven T.; Arias, Renee S.; Hogan, Cliff S.; Martin, Frank N.; Gordon, Thomas R.
ABSTRACT: Macrophomina crown and root rot has become a significant soil-borne disease issue in California. For many locations in the state, the disease is associated with fields that are no longer pre-plant, flat field fumigated with methyl bromide + chloropicrin. Inoculation experiments indicated that some differences in strawberry cultivar susceptibility to Macrophomina phaseolina were seen a short time after the inoculation, but as disease progressed such differences did not persist. Preliminary characterization studies of Macrophomina phaseolina isolates from strawberry indicated that such isolates may have a host preference for strawberry. Macrophomina phaseolina isolates from watermelon, thyme, and apple failed to cause disease in strawberry. Five cover crop species, which can be rotated with strawberry, did not develop disease when inoculated with strawberry isolates. In preliminary analysis using simple sequence repeat markers, isolates obtained from strawberry formed a separate group compared to isolates recovered from other known Macrophomina phaseolina hosts.